2008
DOI: 10.1021/jf800551d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Ester Analysis in Cachaça and Distilled Spirits by Gas Chromatography−Mass Spectrometry (GC−MS)

Abstract: An analytical procedure for the separation and quantification of ethyl acetate, ethyl butyrate, ethyl hexanoate, ethyl lactate, ethyl octanoate, ethyl nonanoate, ethyl decanoate, isoamyl octanoate, and ethyl laurate in cachaca, rum, and whisky by direct injection gas chromatography-mass spectrometry was developed. The analytical method is simple, selective, and appropriated for the determination of esters in distilled spirits. The limit of detection ranged from 29 (ethyl hexanoate) to 530 (ethyl acetate) micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
1
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 25 publications
7
35
1
10
Order By: Relevance
“…The ethyl acetate and ethyl lactate are the major ester compounds present in cachaças according to Nascimento et al 19 All esters, other than ethyl lactate, were found in higher concentrations in the head fraction rather than in the other fractions. Ethyl lactate, the most soluble in water among the esters evaluated, was predominant in the heart and tail fraction.…”
Section: Resultsmentioning
confidence: 94%
“…The ethyl acetate and ethyl lactate are the major ester compounds present in cachaças according to Nascimento et al 19 All esters, other than ethyl lactate, were found in higher concentrations in the head fraction rather than in the other fractions. Ethyl lactate, the most soluble in water among the esters evaluated, was predominant in the heart and tail fraction.…”
Section: Resultsmentioning
confidence: 94%
“…Nas amostras de uísque este éster está presente em concentrações inferiores a 3 mg 100 mL -1 álcool anidro. 11 A baixa concentração de lactato de etila nas amostras de uísque é um indicativo da ausência de Lactobacillus spp durante o processo de fermentação ou um melhor controle do pH e da temperatura no processo fermentativo. A produção de uísque corriqueiramente emprega leveduras selecionadas e um estrito controle da contaminação microbiológica do pé de cuba e da temperatura.…”
Section: Resultsunclassified
“…Cromatografia gasosa acoplada ao detector de espectrometria de massas (CG/EM-MSI) 11 As análises foram realizadas em um cromatógrafo (Shimadzu GC-17A), equipado com um detector de espectrometria de massas (Shimadzu QP5050A) operando no modo de impacto eletrônico (70 eV), monitoramento seletivo de íons (MSI) e injeção direta da amostra no modo split.…”
Section: Volumetriaunclassified
See 1 more Smart Citation
“…Nascimento et al [10] described a qualitative and quantitative high-performance liquid chromatographic analysis of aldehydes in cachaça and in other distilled alcoholic beverages. Nascimento et al [11] determined esters in cachaça and other distilled spirits by gas chromatography-mass spectrometry (GC-MS). More recently, Souza et al [12] applied a comprehensive two-dimensional gas chromatography for the determination of volatile compounds in cachaça.…”
Section: /16mentioning
confidence: 99%